NEWS DISCOURSE ON THE 212 SOCIAL MOVEMENTS: CRITICAL DISCOURSE ANALYSIS ON REPUBLIKA AND MEDIA INDONESIA - Achmad Jamil; Danof Daniel; Amer Qasem (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
The 3rd Defend Islam Action incident on Friday, December 2, 2016, was the biggest rally after the 1998 protest rally. This action created two camps, i.e. supporters of DKI Jakarta Governor, Basuki Tjahaja Purnama, and the camp who demanded his detention. This condition could be seen in mass media news, including in the Media Indonesia newspaper owned by Surya Paloh, Chairman of the National Democratic Party, who supports Basuki Tjahaja Purnama and also in the Republika newspaper which promotes the interests of Muslims. The focus of this study is the existence of different discourses on the news of this 3rd Defend Islam Action. These differences are the result of the interests and ideology of the two media. Media Indonesia’s news discourse did not support the action. On the contrary, Republika pushed for it to be carried out. This study uses the public sphere and hegemony theory which is able to see that in the news text both media have their own interests and ideologies. This study used a critical paradigm with a qualitative descriptive method. Teun Van Dijk's critical discourse analysis model was used in this study. The results of this study indicate that the news coverages of the 3rd Defend Islam Action produced by Media Indonesia and Republika were produced by their editorial staff based on the ideology and hidden interests of the media.